Repetition blindness and the Colavita effect. - Ngo, M; Sinnett, S; Soto-Faraco, S; Spence, C (2010)
People often fail to respond to an auditory target if they have to respond to a visual target presented at the same time, a phenomenon known as the Colavita visual dominance effect. To date, the Colavita effect has only ever been demonstrated in detection tasks in which participants respond to pre-defined visual, auditory, or bimodal audiovisual target stimuli. Here, we tested the Colavita effect when the target was defined by a rule, namely the repetition of any event (a picture, a sound, or both) in simultaneously-presented streams of pictures and sounds. Given previous findings that people are better at detecting auditory repetitions than visual repetitions, we expected that the Colavita visual dominance effect might disappear (or even reverse). Contrary to this prediction, however, visual dominance (i.e., the typical Colavita effect) was observed, with participants still neglecting significantly more auditory events than visual events in response to bimodal targets. The visual dominance for bimodal repetitions was observed despite the fact that participants missed significantly more unimodal visual repetitions than unimodal auditory repetitions. These results therefore extend the Colavita visual dominance effect to a domain where auditory dominance has traditionally been observed. In addition, our results reveal that the Colavita effect occurs at a more abstract, rule-based, level of representation than tested in previous research.